2020
DOI: 10.1038/s41598-020-73467-5
|View full text |Cite
|
Sign up to set email alerts
|

FFA2-, but not FFA3-agonists inhibit GSIS of human pseudoislets: a comparative study with mouse islets and rat INS-1E cells

Abstract: The expression of short chain fatty acid receptors FFA2 and FFA3 in pancreatic islets raised interest in using them as drug targets for treating hyperglycemia in humans. This study aims to examine the efficacy of synthetic FFA2- and FFA3-ligands to modulate glucose-stimulated insulin secretion (GSIS) in human pseudoislets which display intact glucose responsiveness. The FFA2-agonists 4-CMTB and TUG-1375 inhibited GSIS, an effect reversed by the FFA2-antagonist CATPB. GSIS itself was not augmented by CATPB. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…In contrast, butyrate downregulated several IL-1β-induced inflammatory genes encoding chemokines, interleukins, immunoproteasome subunits, and enzymes producing inflammatory mediators. Other studies have also reported on the anti-inflammatory properties of butyrate, which are thought to be mediated through inhibition of NFκB [37][38][39][40]. In vivo downregulation of chemokines such as Cxcl1 and Cxcl10 may be important to reduce the recruitment and activation of immune cells, thereby reducing islet inflammation and improving beta cell function [41].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, butyrate downregulated several IL-1β-induced inflammatory genes encoding chemokines, interleukins, immunoproteasome subunits, and enzymes producing inflammatory mediators. Other studies have also reported on the anti-inflammatory properties of butyrate, which are thought to be mediated through inhibition of NFκB [37][38][39][40]. In vivo downregulation of chemokines such as Cxcl1 and Cxcl10 may be important to reduce the recruitment and activation of immune cells, thereby reducing islet inflammation and improving beta cell function [41].…”
Section: Discussionmentioning
confidence: 99%
“…In primary isolated human islets, butyrate did not significantly stimulate GSIS. Insulin secretion of human islets were inhibited when treated with specific GPR43 agonists [29]. Therefore, it can be speculated that butyrate treatment increased beta cell maturation, but in parallel attenuated GSIS of NPICCs by binding to GPR43.…”
Section: Discussionmentioning
confidence: 99%
“…PA ((S)-2-(4-chlorophenyl)-3,3-dimethyl- N -(5-phenylthiazol-2-yl)butanamide), a synthetic GPR43 agonist, potentiated insulin secretion in isolated murine islets, human islets, and Min6 cells in vitro by increasing intracellular IP3 and Ca 2+ levels in a GPR43-, G q -, and PLC-dependent manner ( 23 ). However, another GPR43 synthetic agonist, 4-CMTB (4-Chloro-α-(1-methylethyl)-N-2-thiazolyl-benzeneacetamide), invariably inhibited GSIS in human pseudoislets, contrary to mouse islets, where it augmented GSIS ( 88 ). This finding that mouse and human islets responded differently to acetate and GPR43 agonists in GSIS assay will require close attention in future studies, since GPR43 is considered as a potential T2D target.…”
Section: Gpcr Signaling Pathways In Metabolismmentioning
confidence: 99%